1993
DOI: 10.1080/07399339309516023
|View full text |Cite
|
Sign up to set email alerts
|

Body temperature and diurnal type in women with seasonal affective disorder

Abstract: Body temperature rhythms and diurnal type were explored in female controls and women with seasonal affective disorder (SAD) before and after phototherapy. Women with SAD reported being more like evening types than did controls. Morning phototherapy advanced the body temperature rhythms of women with SAD, and shifted their morningness/eveningness scores toward the morning end of the continuum. The implications of these results for our understanding of both SAD and depression in women are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2002
2002
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 12 publications
1
9
0
Order By: Relevance
“…The finding that SAD patients during remission had higher MES than controls support the hypothesis of SAD being associated with circadian rhythms, and is in line with a previous study reporting more eveningness in depressed SAD patients and a shift towards morningness after light therapy (Elmore et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…The finding that SAD patients during remission had higher MES than controls support the hypothesis of SAD being associated with circadian rhythms, and is in line with a previous study reporting more eveningness in depressed SAD patients and a shift towards morningness after light therapy (Elmore et al, 1993).…”
Section: Discussionsupporting
confidence: 91%
“…The insufficiency of build-up is similar to the slow build-up in long sleepers (Aeschbach et al, 2001), or in evening chronotypes (Taillard et al, 2003). Since SAD patients (at least subjectively) consider themselves long sleepers, and appear to be more often late chronotypes (Elmore et al, 1993;Putilov et al, 2000;Graw et al, unpublished data), the present finding may be related to these physiological characteristics and not their winter depressive diagnosis per se.…”
Section: Waking Eeg Throughout 30 H Wakefulnessmentioning
confidence: 58%
“…As regards depression, it has been shown that there is a link between eveningness and mood levels both in clinical and healthy samples. 1,2 In line with these data, there is a higher prevalence of evening types among people with seasonal affective disorder (SAD), 3 as well as a positive relationship between eveningness and mood seasonality in healthy young adults and adults. 4,5 It has been found that circadian type is linked to circadian clock-related polymorphisms and it has been suggested that these polymorphisms could also be involved in the susceptibility to SAD.…”
mentioning
confidence: 80%